2019
DOI: 10.1038/s41598-019-47455-3
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 targets the cardiopulmonary system in a robust oral infection mouse model

Abstract: Severe infection with the re-emerging enterovirus 71 (EV71 or EV-A71) can cause cardiopulmonary failure. However, in patients’ heart and lung, viral protein has not been detected. In mouse models, heart disease has not been reported. EV71-infected brainstem is generally believed to be responsible for the cardiopulmonary collapse. One major limitation in EV71 research is the lack of an efficient oral infection system using non-mouse-adapted clinical isolates. In a robust oral infection NOD/SCID mouse model, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
7
2
Order By: Relevance
“…In contrast, in the previous intraperitoneally or intracerebrally inoculated animal models, no obviously positive CVA16 antigen or pathological change was found in the CNS, which demonstrated that CA16 had no signi cant neurotropism in these models [11,14]. Despite some evidence showing that CA16 infection is associated with damage to muscle tissues, we did not observe the apparent relationship between limb paralysis and the presence of infectious particles in the skeletal muscle from nasally infected mice, which is different from previous studies [38,39] and also suggested that infection sensitivity differs slightly between respiratory inoculation and the intraperitoneal-or intracerebral-inoculation route. Consistent with previous studies in orally infected immunode ciency AG129 mice [40], the small quantity of infectious viral RNA in the limbs suggests that limb paralysis might be a consequence of virus neuro-invasion rather than direct damage to limb muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, in the previous intraperitoneally or intracerebrally inoculated animal models, no obviously positive CVA16 antigen or pathological change was found in the CNS, which demonstrated that CA16 had no signi cant neurotropism in these models [11,14]. Despite some evidence showing that CA16 infection is associated with damage to muscle tissues, we did not observe the apparent relationship between limb paralysis and the presence of infectious particles in the skeletal muscle from nasally infected mice, which is different from previous studies [38,39] and also suggested that infection sensitivity differs slightly between respiratory inoculation and the intraperitoneal-or intracerebral-inoculation route. Consistent with previous studies in orally infected immunode ciency AG129 mice [40], the small quantity of infectious viral RNA in the limbs suggests that limb paralysis might be a consequence of virus neuro-invasion rather than direct damage to limb muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, VP1-280T is located near the binding site with the VP2-EF loop and human SCARB2 receptor for viral entry ( Zhou et al, 2019 ). Overall, our current results warrants further studies on the functional significance of these disease-associated mutations in animal models ( Liao et al, 2014 ; Shih et al, 2018 ; Chang et al, 2019 ; Liou et al, 2019 ), once infectious cDNA clones can be successfully isolated from these patients in the future. Furthermore, our findings here could facilitate earlier detection based on the risk score in predicting severe cases infected with EV-A71 in clinical medicine.…”
Section: Introductionmentioning
confidence: 64%
“…Viral strains of EV-A71 were isolated from throat swabs of patients by the Section of Clinical Virology and Molecular Diagnosis, Department of Laboratory Medicine, Changhua Christian Hospital, Taiwan. Virus preparation was as described previously ( Liao et al, 2014 ; Liou et al, 2016 , 2019 ; Chang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggested EV71 infection could skew host TCRβ repertoire and also expand VP1-specific TCRβ CDR3 clones. Although these results may not adapt to other EV71 infection mouse models directly [61][62][63] and could not completely reflect natural situations in human beings due to the limited experimental mouse model and bioinformatic prediction, these findings could partly broaden our knowledge in EV71 pathogenesis and provide an insight in the anti-viral therapy development potentially via manipulating expanded TCRβ CDR3 clones in virus infection.…”
Section: Discussionmentioning
confidence: 87%